PATRIMÔNIO ARQUEOLÓGICO NA CIDADE DE BOM PRINCÍPIO – PIAUÍ: PERCEPÇÕES DE ALUNOS E PROFESSORES DO ENSINO MÉDIO - Luiza de Carvalho Azevedo, Debora; Frazão Santana, Jullyane; Geissiane Aguiar Alves, Maria; Jordânia De Sousa Silva, Maria; Farias Costa, Naide; Araújo de Barros Neto, Pedro; Campelo Veras, Tatiara; Pires Melo, Samuel (Revista Form@re - Parfor/UFPI, 2026)
.